A Comprehensive Review on Novel Lipid-Based Nano Drug Delivery - Sonam Suresh Godase; Nilesh Shrikant Kulkarni; Shashikant Nivrutti Dhole (Advanced Pharmaceutical Bulletin, 2024)
Novel drug delivery system opens the doors towards nano/micro formulation strategies to overcome the challenges associated with the poorly soluble and permeable drugs. Lipid based nanoparticles are widely accepted that includes liposomes, niosomes and micelles which are FDA approved. Such lipid based drug delivery allows delivery for natural phytoconstituents, biopharmaceutical classification system (BCS) class II and class IV drugs are effectively delivered to improve its solubility, permeability and bioavailability. The article provides the recent advances and application of lipid based dosage form for improvement of therapeutic efficacy.